1998
DOI: 10.1901/jaba.1998.31-65
|View full text |Cite
|
Sign up to set email alerts
|

Classroom‐based Functional and Adjunctive Assessments: Proactive Approaches to Intervention Selection for Adolescents With Attention Deficit Hyperactivity Disorder

Abstract: The present investigation evaluated the utility of classroom-based functional and adjunctive assessments of problem behaviors for 2 adolescents who met diagnostic criteria for attention deficit hyperactivity disorder (ADHD) and comorbid oppositional defiant disorder (ODD). For children with ADHD-ODD, environmental classroom variables, when systematically manipulated by teachers, were related to the occurrence and nonoccurrence of problem behaviors. Classroom interventions derived from information that was obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
78
0
4

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(84 citation statements)
references
References 24 publications
(35 reference statements)
2
78
0
4
Order By: Relevance
“…Results of the teacher-implemented functional analysis for both students identified the function of the students' behaviors and indicated that there was a functional relationship between packaged interventions (including curricular modification and self-recording) and increases in ontask behavior. The authors stated that this study added to the literature supporting use of functional behavior assessment procedures by teachers and also reported that teachers found these procedures to be socially acceptable (Ervin et al, 1998). (Iwata et al, 1994).…”
Section: Research On Functional Behavior Assessmentmentioning
confidence: 88%
See 2 more Smart Citations
“…Results of the teacher-implemented functional analysis for both students identified the function of the students' behaviors and indicated that there was a functional relationship between packaged interventions (including curricular modification and self-recording) and increases in ontask behavior. The authors stated that this study added to the literature supporting use of functional behavior assessment procedures by teachers and also reported that teachers found these procedures to be socially acceptable (Ervin et al, 1998). (Iwata et al, 1994).…”
Section: Research On Functional Behavior Assessmentmentioning
confidence: 88%
“…Ervin, DuPaul, Kern, and Friman (1998) investigated the effects of classroombased functional and adjunctive assessments and subsequent intervention packages with two students diagnosed with attention deficit hyperactivity disorder (ADHD) and comorbid oppositional defiant disorder (ODD) in a private school setting. For the first student they used an alternating treatments design to assess the variables affecting the behavior followed by a reversal design to assess the impact of the treatment package.…”
Section: Research On Functional Behavior Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Function-based support is among the areas with strongest empirical support (Carr et al, 1999;Didden et al, 1997;Iwata, Dorsey, Slifer, Bauman, & Richman, 1982Journal of Applied Behavior Analysis 1968). This research shows that interventions guided by FBAs can be implemented with fidelity and result directly in a reduction in problem behavior and improvement in desired behaviors (Brooks, Todd, Tofflemoyer, & Horner, 2003;Burke, Hagan-Burke, & Sugai, 2003;Crone, Hawken, & Bergstrom, 2007;Ervin, DuPaul, Kern, & Friman, 1998;Ervin, Kern, Clarke, DuPaul, Dunlap, & Friman, 2000;Fairbanks et al, 2007;Grow, Carr, & LeBlanc, 2009;Ingram, Lewis-Palmer, & Sugai, 2005;Kern, Childs, Dunlap, Clarke, & Falk, 1994;Kern, Hilt, & Gresham, 2004;Lucyshyn et al, 2007;Newcomer & Lewis, 2004;Preciado, Horner, & Baker, 2009;Smith & Sugai, 2000).…”
Section: Tertiary Preventionmentioning
confidence: 99%
“…Avaliar o rendimento ou desempenho escolar é tarefa árdua tanto para professores quanto para técnicos que enfrentam a falta de instrumentos de medida desenvolvidos e apropriados à nossa cultura, além da complexidade dos processos envolvidos (Cunha et al;2000). No Brasil, é muito reduzida a experiência com instrumentos de avaliação padronizada relativos ao desempenho escolar, e a maior parte das pesquisas, abordando a temática, tem utilizado um instrumento proposto e padronizado por Stein (1994) É na sala de aula que as dificuldades para aprender se concretizam, tornando, assim, comum que as mesmas sirvam de laboratório para investigação e ensaios de avaliação da aprendizagem e mesmo para práticas de intervenção (Greene, 1995;Ervin et al, 1998). A avaliação inicial e referencial do professor pode então ser de grande utilidade para a investigação das dificuldades de aprendizagem (Romero, 1995).…”
Section: Introductionunclassified